Press protest and publics: the agency of publics in newspaper campaigns - Birks, Jen (Sage, 2010)
Campaign advocacy is a common but rarely researched practice in British tabloid journalism. Newspaper campaigns give an account of ‘public opinion’ to politicians, make explicit claims to speak for ‘the public’ and authentically represent them, and also address readers in an unconventional way in order to recruit their support. This article therefore examines the effect to which agency is attributed to readers and other publics in two such campaigns, and argues that publics were portrayed as active only in relation to the newspaper’s activity, and as primarily as reacting emotionally to the problem. The campaigning press promote themselves commercially and politically as quasi-representatives who challenge distant and ‘out of touch’ political representatives with the populist impulses of ‘public’ demands, but without enhancing the democratic process, or publics’ position within it.